Differentiation and integration » Rules for differentiation  


Contents

1. Table with the rules
2. Chain rule
3. Product rule
4. Quotient rule


1. Table with the rules

 Examples
Function Derivative  f (x)  f '(x)
a 0 6 0
ax a 7x 7
axb abxb – 1 8x3
2xsquare root(x) = 2x1.5
4x5 = 4x–5
24x2
3x0.5 = 3square root(x)
–20x–6 = – 20x6
c · f (x) c · f '(x) 2x13 2 · 13x12 = 26x12
f (x) + g(x) f '(x) + g'(x) x4 + 4x 4x3 + 4
f (x) · g(x)

See product rule
f '(x) · g(x) + f (x) · g'(x) (x2  4) · (x3 + 2x + 3) [x2  4]' · (x3 + 2x + 3) +
(x2  4) · [x3 + 2x + 3]'
=
2x(x3 + 2x + 3) +
(x2 – 4)(3x2 + 2)
=
5x4 – 6x2 + 6x – 8
f (x)g(x)

See quotient rule
g(x) · f '(x) – f (x) · g'(x)(g(x))2 4x + 1x2 + 1 (x2 + 1) · 4  (4x + 1) · 2x(x2 +1)2
 =
4x2 + 4 – 8x2 – 2x(x2 + 1)2
 =
–4x2 – 2x + 4(x2 + 1)2
aebx abebx 12 · πsquare root(2) · e2x πsquare root(2) · e2x
e f (x) f '(x) · e f (x) e2x2 – x (4x – 1) · e2x2 – x
a f (x) ln(a) · f '(x) · a f (x) 54x – 1 ln(5) · 4 · 54x – 1
ln(ax) = ln(a) + ln(x) 1x ln(4x) = ln(4) + ln(x) 1x
ln(axb) = 
ln(a) + b · ln(x)
bx ln(3xsquare root(x)) = 
ln(3) + 1.5 · ln(x)
1.5x
alog(f (x)) = ln(f (x))ln(a) 1ln(a) · 1f (x) · f '(x) 3log(3x – 3) = 
ln(3x – 3)ln(3)
1ln(3) · 13x – 3 · 3
sin(ax + b) a · cos(ax + b) sin(12 π · (x – 1)) 12π · cos(12π · (x – 1))
c · cos(ax + b) a · c · sin(ax + b) cos(2x – 1)square root(2) square root(2) · sin(2x – 1)
tan(x) 1cos2(x) = 
1 + tan2(x


2. Chain rule

f (g(x)) has derivative  f '(g(x)) · g'(x)

Two examples of the chain rule:

f (x) = (x2 + 1)5 f (x) = (x2 + 1)5

g(x) = x2 + 1
g'(x) = 2x
f (u) =u5met u = g(x)
f '(u) = 5u4

f '(x) = 5u4 · 2x
f '(x) = 5(x2 + 1)4 · 2x
f '(x) = 10x(x2 + 1)4
f (x) = square root(1 + sin^2 x) f (x) = square root(1 + sin^2 x)

h(x) = sin(x)
h'(x) = cos(x)
g(u) = 1 + u2with u = h(x)
g'(u) = 2u
f (v) = square root(v)with v = g(u)
f '(v) = 1/(2 square root(v))

f '(x) = cos(x) · 2u · 1/(2 square root(v))
f '(x) = cos(x) · 2 sin(x) · square root(1 + sin^2 x)
f '(x) = (sin x cos x)/(square root(1 + sin^2 x))

3. Product rule

p(x) = f (x) · g(x) has derivative  p'(x) = f '(x) · g(x) + f (x) · g'(x)

An example of the product rule and the chain rule:

h(x) = x · square root(x^2 + x) h'(x) = [x]' · square root(x^2 + x) + x · [square root(x^2 + x)]'

h'(x) = 1 · square root(x^2 + x) + x · 2x + 12square root(x^2 + x)
h'(x) = square root(x^2 + x) + 2x2 + x2square root(x^2 + x)
h'(x) = 2(x2 + x) + 2x2 + x2square root(x^2 + x) = 4x2 + 3x2square root(x^2 + x)
Chain rule part
for square root(x^2 + x)
f (x) = square root(x^2 + x)

g(x) = x2 + x
g'(x) = 2x + 1

f (v) = square root(v)with v = g(x)
f '(v) = 1/(2 square root(v))

f '(x) = 12square root(x^2 + x) · (2x + 1)
f '(x) = 2x + 12square root(x^2 + x)

4. Quotient rule

f (x) = g(x)h(x) has derivative f '(x) = g'(x) · h(x) – g(x) · h '(x)(h(x))2


An example of the quotient rule and the chain rule:

k(x) = 5x2 + 3x – 2x2 + 1 k'(x) = [5x2 + 3x – 2]' · (x2 + 1) – (5x2 + 3x – 2) · [x2 + 1]'(x2 + 1)2

k'(x) = (10x + 3) · (x2 + 1) – (5x2 + 3x – 2) · 2x(x2 + 1)(x2 + 1)

k'(x) = (10x3 + 10x + 3x2 + 3) – (10x3 + 6x2 – 4x)x4 + 2x2 + 1

k'(x) = 10x3 + 10x + 3x2 + 3 – 10x3 – 6x2 + 4xx4 + 2x2 + 1

k'(x) = –3x2 + 14x + 3x4 + 2x2 + 1

To top